Synthesis and characterization of La-promoted Ni/SBA-15 catalysts for methane dry reforming - Omoregbe, Osaze (2017)
Methane dry reforming (MDR) is one of the practicable ways of synchronously converting two greenhouse gases (CO2 and CH4) into syngas which is a valuable feedstock for chemical processes such as Fischer–Tropsch synthesis, but the process suffers from catalyst deactivation caused by active metal sintering and carbon formation. Thus, this research investigated the influence of operating parameters including reactant partial pressure and temperature on the activity of 10%Ni/SBA-15 catalyst in MDR reaction. Additionally, the effect of La-promoter on the performance of 10%Ni/SBA-15 catalyst for MDR was studied. Both the 10%Ni/SBA-15 and 3%La-10%Ni/SBA-15 catalysts were synthesised by the incipient wetness impregnation method and characterised using BET surface area, XRD, FESEM, TEM, FTIR, EDX, H2-TPR, NH3-TPD, and Raman analyses. Subsequently, the synthesised catalysts were tested for MDR in a quartz fixed-bed tubular reactor under atmospheric pressure at varying CO2 and CH4 partial pressure of 20–60 kPa, and a reaction temperature of 923-1023 K. Both the unpromoted and La-promoted catalysts exhibited high BET surface area in the range of 303-445 m2 g-1. FESEM and TEM results revealed that the Ni particles were well distributed in the La-promoted catalyst while some clusters were formed on the unpromoted 10%Ni/SBA-15 catalyst. Evaluation of the catalytic activity of the 10%Ni/SBA-15 catalyst in MDR at 923 K gave CH4 and CO2 conversions of 65.3% and 70.3%, which declined within 4 h on-stream at percentage deviations of 26.1% and 17.6%, respectively. The observed deactivation of the unpromoted catalyst with time-on-stream was attributed to favoured Boudouard reaction leading to carbon formation. However, the 10%Ni/SBA-15 catalyst activity improved with appreciable stability as reaction temperature increased from 923 K to 1023 K at percentage increment of 47.5% and 39.6% in CH4 and CO2 conversions, respectively. The improvement in activity of 10%Ni/SBA-15 catalyst at high temperature was ascribed to the endothermicity of MDR reaction and the suppression of Boudouard reaction. Furthermore, CH4 conversion of the 10%Ni/SBA-15 catalyst increased from 91.1% to 98.8% as the CO2 partial pressure (